Diagnosis and Treatment of Acne Inversa/Hidradenitis Suppurativa in China: An Expert Consensus Statement (2021 Version)# - Consensus Writing Group on the Diagnosis and Treatment of Acne Inversa/Hidradenitis Suppurativa in China (Alphabetically); Hong Fang; Xing-Hua Gao; Song-Mei Geng; Heng Gu; Jun Gu; Li He; Xian Jiang; Hong-Zhong Jin; Qiang Ju; Xiao-Jing Kang; Wei Lai; et al. (Wolters Kluwer Health, 2021)
Abstract. Acne inversa/hidradenitis suppurativa is a chronic, recurrent, inflammatory skin disease that affects the pilosebaceous units, causinfollicular occlusion. The etiology and pathogenesis of acne inversa/hidradenitis suppurativa involves internal and external factors such as genetic susceptibility, inflammation and immunity, microorganisms, obesity, and smoking. acne inversa/hidradenitis suppurativa is difficult to treat, and the current aim of treatment is to control the frequency and duration of disease flares and improve the quality of life. Treatment protocols for acne inversa/hidradenitis suppurativa should be selected based on the disease severity grade. Medical treatments include antibiotics, retinoids, biologics, immunosuppressive agents, and antiandrogen agents. Adjuvant treatments include surgery and laser/light therapies. This consensus aims to further standardize the diagnosis and treatment procedures of acne inversa/hidradenitis suppurativa in China to facilitate its diagnosis and treatment.